(3GdYeOI aj UfGYI GdTYQ hfbOgs - (3GdMSf Hf QTjb GdbjQhGfj, CHh Ydj , GHf QTjb,J (B463 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B:(3hhLOJ GdfGS eNJdajf ajg eNJdajf Yf cKjQ s
(3BNQgG (B:s
(3ef HGH GdLhGR hGdUdI (B: (3dGJMSHf GdOfjG HCMSf JCJi HeKdc aCHhddgee ced GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdCOHs